Optimized bioethanol production from banana stem waste via simultaneous saccharification and fermentation with Saccharomyces cerevisiae - Neil Priharto; Agung Setiawan; Dea Indriani Astuti (Universitas Gadjah Mada, 2025)
Indonesia, one of the world’s largest banana producers, generates significant quantities of banana stem waste, leading to environmental challenges. This study explores the potential of converting this lignocellulosic biomass into bioethanol using a combination of steam pretreatment and simultaneous saccharification and fermentation (SSF) with Saccharomyces cerevisiae. The SSF process integrates enzymatic hydrolysis and fermentation, streamlining bioethanol production. The research applied the Taguchi method with an L9(34) orthogonal array to optimize key parameters, including enzyme concentration, particle size, temperature, and pH. Optimal conditions—5% enzyme concentration (v/v), 60 mesh banana powder, 35 °C and pH 5.00—yielded a maximum ethanol concentration of 9 g/L. Enzyme concentration and particle size were identified as critical factors in enhancing bioethanol yield. This study highlights the potential of banana stem waste as a sustainable resource for bioethanol production, contributing to waste reduction and renewable energy development.